Review of cardiometabolic risk factors among current professional football and professional baseball players - Helzberg, J. H.; Camilo, J.; Waeckerle, J. F.; Keefe, J. H. O. (The Physician and Sportsmedicine, 2010)
Data on the development of cardiovascular disease in professional football players are conflicting. Studies have documented a higher prevalence of obesity, lower high-density lipoprotein cholesterol levels, increased left ventricular and left atrial size, and higher prevalence of metabolic syndrome in former professional football linemen compared with nonlinemen. It has been suggested that former National Football League players are at risk for early cardiovascular disease and premature death. A print media report in 2006 indicated an increased prevalence of cardiovascular disease and early mortality in professional football players compared with professional baseball players. However, there has been little scientific evaluation of cardiovascular risk factors in professional baseball players. Our data suggest that there is increased cardiovascular disease risk in football players, but this is limited to heavier linemen. In preliminary studies, baseball players do not appear to demonstrate the same increased risk. However, caution should be used in the interpretation of increased cardiovascular disease risk, as it does not necessarily translate into early increased mortality.